Public Relations Management Strategy in Increasing Public Interest in Islamic Educational Institutions - Yenni, Yenni; Sayuti, Imam; Alwizra, Alwizra; Putri, Sinta Westika; Marwah, Marwah; Iskandar, M. Yakub; Aminudin, Wan Sofea Adlin Binti Wan (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2023)
Schools will be in demand by the community if they can provide satisfaction to the community, especially regarding their educational programs. Apart from that, schools must also be able to provide interesting, fast, and accurate information to the community so that people can see, hear, and feel directly or indirectly what the school produces, especially for its students. The dissemination of school information to the public is done by a public relations officer. In carrying out his role, a public relations person has a strategy agreed upon by the school as a policy that will be implemented as a school program. This research aims to find out what the public relations management strategy is in Islamic educational institutions so that many people are interested. This research uses qualitative methods with a case study approach by taking the research location at the Islamic Education Institute. Data sources were taken from twenty-five people consisting of the principal, deputy principal for public relations, three core school committee administrators, ten parents, five community members, and five students. Interviews were conducted using in-depth interviews selected using the technique of purposive sampling. All data was analyzed using interactive techniques by Milles and Huberman. The results of the analysis show that the public relations management strategy implemented by Islamic educational institutions is carried out by approaching the community through activities: i) demonstrations from schools; ii) community involvement; and iii) establishing friendships. School demonstration activities carried out include preaching in mosques, prayer rooms, and ta'lim assembly forums, and holding religious activities by displaying students' abilities such as religious poetry, short lectures, hadrah, and qasidah. Community involvement, such as involving the community in Islamic Holiday Commemoration events held by the school. Annual routine gatherings, such as the Tahfidz graduation ceremony, which is held grandly by presenting community leaders, government elements, and parents of students. This research can be used as initial data for future researchers studying this problem in different contexts and issues.